Do ESG and Diversity Scores Predict Global Firms’ Environmental Innovation? - Saydam, Mehmet Bahri; Olorunsola, Victor Oluwafemi; Arici, Hasan Evrim; Koseoglu, Mehmet Ali (SAGE Publications, 2024)
Environmental innovation (EI) is fundamental to sustainable development goal (SDG) number 9. Indirectly, it contributes to the achievement of SDG 7 by laying the groundwork for producing renewable energy. Firms involve environmental, social, and governance (ESG) and diversity practices to achieve sustainable success. ESG and diversity scores on EI need to be predicted, yet EI predictors are few in the research. Our institutional theory-based study examines whether ESG and diversity scores influence EI scores in multinational organizations. The dataset comprises information from the Refinitiv Eikon database, including 430 publicly traded firms worldwide throughout 2021. The results of our study indicate that the environmental pillar score, ESG, and workforce score are the three most significant factors for calculating enterprises’ EI scores. This research provides valuable insights into enhancing sustainability practices and fostering innovation in global firms, offering a practical roadmap for businesses striving to achieve these objectives.
Keywords: 9. Industry and infrastructure; 11. Sustainability; 7. Clean energy; 12. Responsible consumption